Moonshot. Volume 3 : the indigenous comics collection - LaPensée, Elizabeth; Sheyahshe, Michael A., 1975-; Dillon, Grace L. (Avani, 2020)
Provides an anthology of graphic novel stories about indigenous peoples exploring various themes of trauma, greed, and survival through stories that merge tradition with futurism and fantasy.